Efektivitas pijat kaki dan aromaterapi lavender mengurangi gangguan insomnia pada lansia - Clara Santa Maria Yanti Tumanggor; Rika Yulenda Sari; Djunizar Djamaludin (Holistik Jurnal Kesehatan, 2021)
The effectiveness of foot massage and lavender aromaterapy towards the treatment of insomnia in elderlyBackground : Elderly people with insomnia tend to be easily stressed and depressed. When other people are asleep, they are not sleepy, their eyes cannot be closed all night, and sometimes they can make frustrations to force themselves to sleep. Causing various things that interfere with the activity of the next day, such as difficulty concentrating, loss of mood, lack of enthusiasm, and the occurrence of emotional disturbances that are difficult to control.Purpose: To find out alternative therapies using the method (foot massage and lavender essential oil) in the treaty of insomnia in the elderlyMethod: A quasi pre and post-experimental design with intervention and control groups. The samples were taken using purposive sampling with 48 participants. The research instrument used SOP massage and aromatherapy and insomnia IRS questionnaire.Results: The effectiveness of foot massage and lavender aromatherapy on reducing insomnia in the elderly at Tresna Werdha nursing home, Natar with p-value = 0.060.Conclusion : The evidence in effectiveness of alternative therapies using the method (foot massage and lavender essential oil) in the treaty of insomnia in the elderly. I recommend it for caring in the elderly at nursing homes, which is to improve sleep quality in the elderly by providing foot massage therapy and lavender aromatherapy.Keywords : Foot massage; Essential oil lavender; Aromatherapy, InsomniaPendahuluan : Lansia dengan insomnia cenderung mudah stress  dan depresi. Pada saat orang lain sudah tidur, merekatidak mengantuk, mata tidak dapat terpejam sepanjang malam, dan terkadang dapat membuat frustasi untuk memaksakan diri untuk tidur.Sehingga menyebabkan berbagai hal yangmenganggu aktivitas esok harinya, seperti sulit untuk berkonsentrasi, hilang mood, kurang bersemangat,dan terjadinya gangguan emosi yang sulitdikendalikan.Tujuan :Diketahui Perbedaan Efektifitas Pijat Kaki Dan Aromaterapi LavenderMetode :Design penelitian menggunakan desain quasi ekperimen pre dan post dengan kelompok intervensi yang berbeda. Sampel diambil menggunakan purposive sampling dengan jumlah 48 partisipan. Yang dibagi 2 kelompok masing-masing 24 pada kelompok terapi pijat kaki dan aromaterapi lavender. Sebelum diberikan IRS dilakukan pemeriksaaan MMSE. Untuk mengetahui gangguan kesehatan mental dan dijadikan partisipan. Instrument penelitian ini  ada 11 pertanyaan IRS menggunakan SOP pijat dan aromaterapi lavender.Hasil :Terdapat perbedaan efektifitas pijat kaki dan aromaterapi lavender terhadap penurunan insomnia pada lansia di Panti TresnaWerdha Daerah Natar Tahun 2019 dengan (p value = 0.060).Simpulan :Disarankan bagi pelayanan di posyandu lansia dan panti jompo, yaitu untuk meningkatkan kualitas tidur pada lansia dengan memberikan terapi pijat kaki dan aromaterapi lavender.